PENGEMBANGAN EKOWISATA BERBASIS MASYARAKAT DI PULAU HARAPAN TAMAN NASIONAL KEPULAUAN SERIBU, JAKARTA - Hadiwinata, Rizki; AT, Mulyadi; Rusli, Abdul Rahman (Universitas Nusa Bangsa, 2014)
Implementation of research activities conducted in the area of Hope Island Thousand Islands National Park . The purpose of this research is ( i ) Identify the potential of tourism in Hope Island TNKpS , ( ii ) Identify the readiness of the community in the development of community-based ecotourism ( iii ) Developing a community-based ecotourism in the area of Hope Island TNKpS . Data on the public , managers and visitors obtained by distributing questionnaires and interviews . Respondent data retrieval community and visitors conducted by interview and questionnaire , sampling methods conducted by purposive sampling method . Purposive sampling method used to obtain data on natural resources and human resources at the Hope Island , while the data on perception , motivation , participation and public interest is taken by using the questionnaire . Meanwhile , the development of community-based ecotourism in Hope Island , formulated using SWOT analysis approach . Data were analyzed using SWOT table .Research results indicate that the potential for ecotourism resources contained in the Hope Island which can be used as a tourist attraction and cultural landscape of the Hope Island itself, from the readiness of the community , the majority of the community supports the development of ecotourism in Hope Island , based on the SWOT matrix , strategy higher in priority to the development of ecotourism activities in Hope Island is a strategy that combines the strengths and opportunities is developing a program of community-based ecotourism activities that combine the potential of nature and culture of Hope Island to attract visitors